The role of particle surface functionality and microstructure development in isothermal and non-isothermal crystallization behavior of polyamide 6/cellulose nanocrystals nanocomposites. (19th December 2016) - Kashani Rahimi, Shahab; Otaigbe, Joshua U.
Abstract: Polyamide 6 (PA6)/cellulose nanocrystal (CNC) and aminopropyl triethoxy silane (APS) - modified CNC nanocomposites were prepared by in situ anionic ring opening polymerization and subsequent melt extrusion. The morphological observation of these hybrid systems revealed that the non-modified nanocrystals developed a network-like fibrillar structure while the APS-modified CNCs were finely dispersed mostly as individual whiskers. The isothermal and non-isothermal crystallization kinetics was extensively studied with emphasis on the effects of CNC surface functionality and the subsequent microstructure development on crystallization behavior of these novel nanocomposite systems. The non-modified CNC particles with corresponding fibrillar microstructure were found significantly hinder the crystallization process and spherultic growth of polyamide 6 chains under both isothermal and non-isothermal conditions. On other hand, the surface modified cellulose nanocrystals with improved sub-micron dispersion enhance crystal nucleation in early stages of crystallization while imposing opposite effect in later stages of crystallization resulting in development of relatively smaller defective spherulitic structures. Graphical abstract: Highlights: Morphology and surface functionality of cellulose nanocrystals controls the crystallization behavior of polyamide 6 hybrids. Aminosilane surface modification of cellulose nanocrystals improves dispersion and morphology in polyamide 6 nanocomposites. While unmodified nanocrystals hinder the polymer crystal growth, surface modification enhances the crystal nucleation rate.